Membangun Negara Hukum Pancasila Yang Berkeadilan Dan Bermartabat - Rafly Hakim; Muhammad Evan Kurnia (Jurnal Relasi Publik, 2023)
This research article has the title "Building a Justice and Dignified Pancasila Law State". In this study, a qualitative method was applied using a normative juridical approach. The data that will be used later is related data from a book, academic writing, report or other written additional source. The source of the data collection correlates with the title under study, the data is collected from main legal sources as well as additional legal sources. The aim of this study is to examine whether the Pancasila legal state has a system that is justice and dignified for its people. The theories used are theories that correlate with the rule of law. The results of the discussion and analysis show that the Pancasila legal state has not fully realized a justice and dignified system. After knowing this, this article will examine how the Pancasila legal state can fulfill these two aspects with efforts to build and reorganize so that the Pancasila legal state can create a system that is justice and dignified for society.